Sacrificial Kings and Martyred Rebels: Charles and Rainborowe Beatified - Rachel Willie (Etudes Epistémè)
In a dramatic end to Civil War, in January 1649, England witnessed the public execution of Charles I. After this event, the iconography of ‘Charles the Martyr’ was frequently used to explicate royalist grief, and to comprehend the execution of the anointed king. This essay addresses three dramatic works that were printed in the aftermath of regicide to examine how they respond to the execution and engage with martyrological discourse. Whereas A Tragi-comedy Called New-Market Fayre (1649) focuses upon the sale of the late king’s goods to flirt with notions of reliquary and address the value of the monarch’s material goods, The Famous Tragedie of Charles I (1649) narrates the regicide and styles Charles a martyr. However, the discourse is destabilised by the appearance of Colonel Rainborowe, a radical parliamentarian who was also depicted as a martyr by his supporters. At the Restoration, The Famous Tragedie was revised to celebrate the death of Oliver Cromwell. Cromwell’s Conspiracy (1660) presents the regicide as pre-figuring future royalist suffering before the triumphal restoration of the monarchy. These conflicting iconographies complicate our understanding of matyrological discourse and how it might be adopted as a way to understand the 1649 regicide.